Developing Learning-based Instagram Media on Derivative - Bimba Dhiwangkara; I Nyoman Arcana; Annis Deshinta Ayuningtyas (Universitas Tidar, 2020)
This study aims to develop learning media using Instagram and determine its feasibility. This research method used Research and Development (R&D) with the ADDIE development model through 5 stages, namely Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SMA N 1 Ngemplak. The data collection technique used a validation questionnaire conducted by two teachers and one lecturer and students response questionnaire. The data analysis techniques were descriptive qualitative and quantitative. The result of this research was a derivative learning media in the form of videos presented through Instagram. The feasibility test results showed that the learning media had met three eligibility criteria for learning media. The assessment of media and material experts showed that learning-based Instagram media was in the good category. Based on students' assessment, learning media's feasibility based on Instagram social media was good to use. The correlation between the students response questionnaire and the learning outcome test also showed a unidirectional and significant correlation. It indicated that there was a correspondence between the questionnaire scores and the learning outcome test scores. Based on these results, learning media through Instagram social media is suitable for the learning process.